64 Evaluating the Acute use of Rotigotine Patch for Dopaminergic Replacement in An Inpatient Population. (6th February 2020) - Ibrahim, H; Cavanagh, A; Richfield, E W
Abstract: Introduction: Rotigotine, a trans-dermal dopamine agonist (DA), can be used acutely for inpatient populations and is an option in end of life (EoL) care for people with Parkinson's disease (PD) where enteral (oral or naso-gastric) routes are no longer available or appropriate. Concerns regarding acute use of DAs in hospital include: i) difficulty achieving dopaminergic equivalence; ii) promotion of delirium; and iii) promotion of terminal agitation at EoL. Methods: We retrospectively evaluated acute inpatient Rotigotine use in a UK teaching hospital. Prescriptions between January-June 2018 were identified from the pharmacy database and relevant inpatient records were analysed. The OPTIMAL calculator was used as a gold standard for dopaminergic conversion. Results: 33 eligible inpatients were identified. 13 (39%) patients were prescribed the recommended dose of Rotigotine; 7 (21%) higher and 13 (39%) lower than recommended dose. Of 22 (66%) patients with delirium, 18 (82%) inappropriately received the higher dose. 12 (36%) patients developed new or worsening delirium; and 6 (18%) developed new or worsening hallucinations. 19 (58%) patients were dead at time of evaluation with median survival of 22 days (range 1-207). For patients prescribed Rotigotine for EoL (n=13), median survival was 15 days (range 1-62); for patients not prescribed Rotigotine for EoL (n=20), median survival was 81 days (range 6-207). Of 13 (39%) patients prescribed Rotigotine for EoL, 9 (69%) had evidence of terminal agitation. Conclusions: Acute conversion to Rotigotine remains problematic, despite availability of validated tools. Inappropriate dosing may precipitate or worsen delirium. Acute prescription of Rotigotine appears to act as a proxy marker for poor prognosis and could be a red flag for triggering advanced care planning. Little is published regarding use of Rotigotine at EoL, this data raises concerns regarding risk of terminal agitation and is an important area for further study.